Habitat associations of stream fishes in protected tallgrass prairie streams - Martin, Erika C.; Whitney, James E.; Gido, Keith B.; Hase, K. J. (My University, 2013)
Describing fish habitat associations and their relevance to conservation remains a central challenge in stream fish ecology. Unfortunately, there are limited opportunities to investigate these associations in unaltered systems and identify critical habitats used by native fishes. Investigation of fish habitat associations in tallgrass prairie is especially vital, owing to their widespread destruction. Our study aim was to identify habitat factors associated with the distribution and density of fishes in two protected tallgrass prairie stream watersheds in eastern Kansas: Kings Creek on the Konza Prairie Biological Station (KPBS) and Fox Creek on the Tallgrass Prairie National Preserve (TPNP). We sampled fishes and measured eight habitat variables at three sites on KPBS (2006–2011) and four sites on TPNP (2008–2011). Multiple regression suggested that species richness was positively associated with pool area (partial r  =  0.70) and discharge (partial r  =  0.50) in Fox Creek (df  =  15, Adj. R²  =  0.60, P < 0.001). In Kings Creek, species richness was only associated with pool area (df  =  17, R²  =  0.44, P < 0.001). Redundancy analyses showed common prairie fish species exhibit ontogenetic habitat associations, partitioning adults in deep and juveniles in shallow pools. Strong species area relationships in these minimally altered systems indicates large volume habitats have greater species richness, suggesting water diversions or extractions that reduce habitat are likely to cause declines in native biodiversity.
Keywords: Conservation; Fish habitat; Tallgrass prairie; Stream watersheds; Konza Prairie Biological Station; Tallgrass Prairie National Preserve